Growth and development in an extremely low birth weight infant with osteopenia of prematurity: a case report - Syifa Armenda; Tunjung Wibowo; Mei Neni Sitaresmi (Indonesian Pediatric Society, 2022)
Caring for extremely low birth weight (ELBW) infants remains a challenge in developing countries due to high morbidity and mortality rates. In Dr. Sardjito Hospital, Yogyakarta, the ELBW survival rate was 39.3%.1 Expected outcomes of these ELBW survivors are increased risk of mortality during the infant period and short term as well as long term complications.2 Osteopenia of prematurity is a comorbidity that can interfere with longterm growth and neurodevelopment.3 Osteopenia of prematurity is found in approximately 55% of babies with ELBW.4 Antenatal demineralization is aggravated by improper nutritional interventions during perinatal care and post-discharge care. This comorbidity is asymptomatic in the infant’s early life, but later contributes to linear growth failure, delayed teeth eruption, respiratory problems, and bone fractures in ELBW babies.3 Early detection and prompt management of osteopenia of prematurity are needed for all ELBW infants. Here we present a case of an ELBW infant with osteopenia of prematurity who we observed for 18 months. The child underwent multidisciplinary interventions for modifiable prognostic factors to support optimal achievement of growth and neurodevelopment.